Understanding day–night differences in dust aerosols over the dust belt of North Africa, the Middle East, and Asia - J. Z. Tindan; J. Z. Tindan; Q. Jin; B. Pu (Atmospheric Chemistry and Physics, 2023)
Utilizing the well-calibrated, high-spectral-resolution equal-quality performance of daytime and nighttime (09:30 and 21:30 local solar Equator-crossing time (local solar ECT)) products of the Infrared Atmospheric Sounder Interferometer (IASI) from the Laboratoire de Météorologie Dynamique (LMD), this study investigates the day–night differences in dust aerosols over the global dust belt of North Africa, the Middle East, and Asia. Both daytime dust optical depth (DOD) and nighttime DOD at 10 µm show high consistency with solar and lunar observations of coarse-mode aerosol optical depth (CAOD) from AErosol RObotic NETwork (AERONET) sites across the dust belt, with correlation coefficients of 0.8–0.9 for most sites. Both IASI DOD and dust layer height show a significant (95 % confidence level) day–night difference over the major dust sources within the dust belt. Daytime DOD over the central to northern Sahara, the central to eastern Arabian Peninsula, and the Taklamakan Desert is significantly higher than that of nighttime but lower than nighttime over the southern Sahel to the Guinea Coast and the western to central Indian subcontinent in the annual mean. The magnitude of the day–night differences in DOD is larger and more evident in boreal winter and spring than in other seasons. The positive day–night differences in DOD (i.e., higher daytime values than nighttime) over the central Sahara, the Middle East, and Asia are likely associated with greater dust emissions driven by higher dust uplift potential (DUP) and stronger wind speeds during daytime. Dust layer heights demonstrate negative day–night differences over dust source regions in the central Sahara, central Arabian Peninsula, and Taklamakan Desert and positive height differences in the southern Sahel to the Guinea Coast, southern parts of the Arabian Peninsula, and large parts of the Indian subcontinent. The higher dust layer height over the Guinea Coast and the Indian subcontinent during the daytime is associated with a deeper planetary boundary layer height and greater convective instability during daytime than nighttime, which promotes vertical transport and mixing of dust aerosols. The corresponding lower daytime DOD over the Sahel and the Indian subcontinent indicates a possible dilution of dust aerosols when they are transported to higher altitudes by convection where they are more susceptible to horizontal transport.